The dynamic nexus among carbon dioxide emissions, energy consumption, and tourism development in Sri Lanka - Maheswaranathan, Sarojini (Energy Economics Letters, 2024)
The study examines the dynamic nexus among carbon dioxide emissions, energy consumption, and tourism development in Sri Lanka. The tourism sector is one of the fastest-growing industries throughout the globe. This sector significantly contributes to the national development of a country in various ways, not only in developed countries but also in developing countries. However, activities related to the tourism sector contribute to environmental damage, such as transportation, establishing tourism destinations, discouraging wages, high presume on endangered species, and developing foreseeing fire, etc. Scholars for various studies have found conflicting results about the relationship between growing tourism and environmental degradation. Therefore, based on the ARDL cointegration analysis for the period 1990-2019 in Sri Lanka, this paper examines whether the tourism development has contributed to environmental damage, energy consumption, and economic growth. Statistical analysis of the data demonstrates that CO2 emissions in Sri Lanka are negatively correlated with tourist arrival (TR) but positively correlated with tourism receipt (TR) and energy consumption (EC) in the long term. Further, the findings highlight that there is no significant relationship between CO2 emissions and economic growth in Sri Lanka. The findings of this research ensure that the tourism industry can adjust to shifting energy conditions and economic dynamics by pointing policymakers in the direction of workable strategies that strike a balance between energy efficiency, economic growth, and sustainable tourism development.